2017
DOI: 10.3390/ma11010008
|View full text |Cite
|
Sign up to set email alerts
|

Organic Thin Film Transistors Incorporating Solution Processable Thieno[3,2-b]thiophene Thienoacenes

Abstract: Bottom-gate bottom-contact organic thin film transistors (OTFTs) were prepared with four novel star-shaped conjugated molecules containing a fused thieno[3,2-b]thiophene moiety incorporated either in the core and/or at the periphery of the molecular framework. The molecules were soluble in CS2, allowing for solution-processing techniques to be employed. OTFTs with different channel geometries were characterized in both air and vacuum in order to compare environmental effects on performance. Blending the small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The ambipolar behavior for PCPF 60 –SWNT and IsoSol‐S100 was significantly altered when the devices were evaluated under vacuum ( P < 0.1 Pa), with the majority charge carrier switching to electrons. Suppressed hole transport under vacuum was observed for PCPF 60 –SWNT and IsoSol‐S100 (Table S4, Supporting Information), an effect seen previously in SWNT OTFTs, as well as for both p‐type semiconducting polymers and small molecules . Surprisingly, PCPF 60 –SWNT‐EP still retains a significant amount of p‐type character when analyzed in vacuum, potentially by lowering the contact resistance between the nanotubes and the gold electrodes through the polymer phase which has a deeper HOMO level .…”
Section: Resultsmentioning
confidence: 55%
“…The ambipolar behavior for PCPF 60 –SWNT and IsoSol‐S100 was significantly altered when the devices were evaluated under vacuum ( P < 0.1 Pa), with the majority charge carrier switching to electrons. Suppressed hole transport under vacuum was observed for PCPF 60 –SWNT and IsoSol‐S100 (Table S4, Supporting Information), an effect seen previously in SWNT OTFTs, as well as for both p‐type semiconducting polymers and small molecules . Surprisingly, PCPF 60 –SWNT‐EP still retains a significant amount of p‐type character when analyzed in vacuum, potentially by lowering the contact resistance between the nanotubes and the gold electrodes through the polymer phase which has a deeper HOMO level .…”
Section: Resultsmentioning
confidence: 55%
“…The largest impact on SiPc device performance was the characterization atmosphere, for which we initially evaluated in an evacuated chamber ( P < 0.1 Pa) and then in air at atmospheric pressure after the devices had been removed from vacuum for 5 min. While our previous studies had looked at this comparison for carbon nanotubes wrapped in semiconducting polymers, P‐type small molecules, and conjugated polymers, we have not yet examined this effect on N‐type small molecules, which are particularly sensitive to oxygen. Table 2 summarizes the changes observed for a single set (one substrate) of devices for each material, with Figure showing sample transfer curves under each condition for material 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has recently found signicant changes in P-type small molecules when tested in air compared to vacuum (P < 0.1 Pa) 46 and demonstrated differences in temperature response under these conditions for two P-type semiconducting polymers. 31 Therefore, we characterized these CuPc and F 16 -CuPc devices at discrete temperatures ranging from T ¼ 25 C to T ¼ 90 C in air and from 25 C to T ¼ 100 C in vacuum.…”
Section: Effect Of Otft Operation Temperaturementioning
confidence: 98%